Beyond databases, architectures and structures : paving the road to smart data processing and analysis : 15th International Conference, BDAS 2019, Ustroń, Poland, May 28-31, 2019, Proceedings /: paving the road to smart data processing and analysis : 15th International Conference, BDAS 2019, Ustroń, Poland, May 28-31, 2019, Proceedings. (2019) - Unknown
No abstract available